AN ANALYSIS OF TEACHER’S METHOD IN TEACHING READING COMPREHENSION IN MAS PONDOK PESANTREN TUNAS HARAPAN - Shelphi Sarini; Melda Yeni; Sri Erma Purwanti (J-Shelves of Indragiri (JSI), 2023)
The importance of this research is to find out the method that teachers use in reading comprehension. This research was conducted at MAS Pondok Pesantren Tunas Harapan Tembilahan. The research used descriptive qualitative with two instruments, namely questionnaire and interview to find and analyze the data collected by the researcher during the research. The population is 1 population and 1 sample, the subject of this research was the English teacher at MAS Pondok Pesantren Tunas Harapan Tembilahan. Data were collected using questionnaires and interviews. Which consists of 13 statements and 4 questions. The results of this study indicate that, the English teacher at MAS Pondok Pesantren Tunas Harapan Tembilahan used 3 dominant methods namely, the phonic method, the language experience approach, and quantum teaching, but based on the interview the teacher said that she used read aloud, the teacher felt that the method was effective because it can help students overcome their difficulties in reading comprehension.